Synthesis Characterization and Biological Activities of 4-Hydroxycoumarin Derivatives - Obi, Juliana Chineze; Ezenwa, Tagbo E.; Vera, Ezigbo (European Journal of Scientific Exploration, 2019)
Three varieties of 4-hydroxycoumarin derivatives (1a-c) were synthesized by reacting an appropriate acetophenone with diethyl carbonate in the presence of sodium hydride, at reflux for 3 hours. The products were obtained in good yields (62-67%). These 4-hydroxycourin derivatives serve as precursors for the synthesis of symmetrical analogues of dicoumarol (4a) which subsequently undergo C-C reductive cleavage using sodium cyanoborohydride (NaBH3CN) to give asymmetrical dicoumarol (2a-e). The enzyme assay investigation revealed that compounds (2a-e) exhibit moderate to good inhibitory potency towards NAD(P)H:oxidoreductase quinine 1 (NQO1) enzyme. The purity and structural identities of all the synthesized compounds were confirmed by melting point, mass spectrometry, IR, 13C and 1H NMR spectroscopy.